Performance evaluation of high-performance concrete mixes incorporating recycled steel scale waste as fine aggregates - Adnan Nawaz; Saad Abdulrahman Hussain; Rana Faisal Tufail; Hafiz Waheed Iqbal; Tahir Mehmood; Panumas Saingam; Wael Alattyih; Jawad Ahmad (Results in Engineering, 2024)
In this study, steel-scale waste (SSW), a byproduct generated during the manufacturing of steel, was investigated as a potential alternative to natural fine aggregates (sand) for preparing high-performance concrete (HPC). Three grades of sand and SSW with different particle sizes were mixed in varying combinations. Three different compaction techniques (loose, tamped, vibration) were employed. The optimum packing density for both SSW and natural aggregates was achieved using the vibration compaction method. Since the combination of 50% sand and 50% SSW exhibited the best packing density for both materials, this bi-grade mixture was selected for the mix preparation. The mechanical tests (compressive strength, flexural strength) and durability assessment (bulk water sorptivity, rate of water absorption, chloride ion penetration) were performed to achieve the desired objectives. The specimens were exposed to two different curing regimes i.e., normal curing and heat curing at elevated temperature. A significant increase in compressive and flexural strength was observed with the increased content of SSW. A compressive strength as high as 140 MPa was obtained for the HPC mix containing SSW aggregates and steel fibers. The replacement ratio of SSW was optimized to achieve better strength and durability. Experimental results of normal and heat curing concluded that heat curing was found to be more effective as compared to the conventional curing method. Experimental results showed that heat curing was more effective than conventional curing methods in improving the performance of the concrete. • Steel scale waste (SSW) was used as fine aggregates for high-performance concrete • Vibration compaction method resulted in the highest packing density of aggregates • Heat curing improved compressive strength to a maximum of 140 MPa • Steel fiber incorporation enhanced both compressive and flexural strengths • Optimized SSW content improved mechanical and durability performance of HPC mixes
Keywords: Recycled Aggregate Concrete Performance; Innovative concrete reinforcement materials; Innovations in Concrete and Construction Materials